A cyanide-bridged wheel featuring a seven-coordinate Mo(iii) center. Issue 14 (29th January 2019) - Kempe, David K.; Dolinar, Brian S.; Vignesh, Kuduva R.; Woods, Toby J.; Saber, Mohamed R.; Dunbar, Kim R.
Abstract : A new, cyanide-bridged Mo6 Ni12 wheel shows ferromagnetic coupling. Abstract : A new cyclic molecule incorporating [Mo III (CN)7 ] 4− has been characterized by single crystal X-ray methods, SQUID magnetometry and theoretical calculations. The wheel molecule [Mo III (CN)7 ]6 [Ni(L)]12 (H2 O)6 exhibits ferromagnetic Mo–Ni coupling which did not exist for the previously reported octacyanometallate analogue [Mo IV (CN)8 ]6 [Ni(L)]12 (H2 O)6 . These results indicate that known supramolecular architectures incorporating octacyanometallates can be used as platforms for making new molecules incorporating seven-coordinate cyanide precursors.